Sémiotique du groupe chez Flaubert - Bernard Gendrel (Flaubert: Revue Critique et Génétique)
Starting from the observation of the omnipresence of moments of sociability in Flaubert's work, even for the most solitary characters, this article questions the place of the group in the Flaubertian semiotic system. Although some configurations (religious ceremonies, meals, ball or theater evenings, political meetings, etc.) are already used by the literary tradition, the games of modifications, enrichments or displacements operated at the different levels of the “parcours génératif” allow very often, as Greimas put it, to “produce the unexpected with almost nothing”.